Peningkatan Mutu Kertas Cetak A Berbasis Kulit Talas Dan Serat Sawit Pada Sifat Fisis - Sari, Devi Kumala; Jumiati, Ety; Daulay, Abdul Halim (Rekayasa Material, Manufaktur dan Energi, 2026)
Paper is a thin material in the form of sheets that is one of the basic needs used by the community, paper is produced from the compression of fibers derived from pulp containing cellulose. This study aims to determine the characteristics of the paper produced and to determine the effect of the composition of the mixture of taro peel pulp and oil palm fruit fiber on paper quality. This study used the soda method, with variations in the weight of samples A (65%: 35%), B (45%: 55%), and C (25%: 75%). Taro peel and oil palm fruit fiber were first cooked with a 10% acetic acid solution, then bleached using a 10% H₂O₂ solution, then dried. The characterization results of the samples showed that sample C was the optimum sample with a grammage test value of 88 g/m2, a bulk test value of 1.25 cm3/g, and a SEM test value of 9,7089. This value shows that sample C has fulfilled some of the standard of SNI 7274:2008, so it can be concluded that the composition of taro peel pulp and oil palm fruit fiber produces paper with quite good quality.